Carbon nanotube composite and carbon nanotube composite bundle wire

CN122996035APending Publication Date: 2026-10-27SUMITOMO ELECTRIC INDUSTRIES LTD +1
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202580021569.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2024-03-28
Filing Date
2025-01-21
Publication Date
2026-10-27

Smart Images

  • Figure CN122996035A_ABST
    Figure CN122996035A_ABST
Patent Text Reader

Abstract

A carbon nanotube composite, wherein the carbon nanotube composite has a carbon nanotube, and a core-shell nanoparticle attached to the carbon nanotube, the core-shell nanoparticle including a core composed of iron, and a shell having iron and sulfur that coats the core, a percentage of the number of atoms of the sulfur with respect to a total of the number of atoms of the iron and the sulfur in the core-shell nanoparticle being 6% or more and 45% or less.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This disclosure relates to carbon nanotube composites and carbon nanotube composite assembly lines. This application claims priority to Japanese Patent Application No. 2024-054384, filed March 28, 2024. The entire contents of that Japanese Patent Application are incorporated herein by reference. Background Technology

[0002] In recent years, the development of lithium-sulfur batteries, which exhibit a theoretical energy density approximately 2 to 3 times higher than existing lithium-ion batteries, has been progressing. Summary of the Invention

[0003] The carbon nanotube composite disclosed herein comprises carbon nanotubes and core-shell nanoparticles attached to the carbon nanotubes. The core-shell nanoparticles comprise a core composed of iron and a shell containing iron and sulfur covering the core. The percentage of the number of sulfur atoms in the core-shell nanoparticles relative to the total number of iron and sulfur atoms is 6% or more and 45% or less. Attached Figure Description

[0004] Figure 1 This diagram is used to illustrate conventional methods for manufacturing carbon nanotubes.

[0005] Figure 2 This is a diagram used to illustrate the manufacturing method of the carbon nanotube composite involved in Embodiment 1.

[0006] Figure 3 This is a transmission electron microscope image of the carbon nanotube composite obtained in sample 5. Detailed Implementation

[0007] [The problem this disclosure aims to solve] In lithium-sulfur batteries, sulfur is used as the positive electrode, but sulfur and its compounds have low conductivity and cannot be directly used as electrode materials. Therefore, there is a need for a material containing sulfur and possessing good conductivity.

[0008] Therefore, the purpose of this disclosure is to provide a material containing sulfur and having good electrical conductivity.

[0009] [The Effects of This Disclosure] According to this disclosure, a carbon nanotube composite that is a sulfur-containing material with good electrical conductivity can be provided.

[0010] [Description of embodiments of this disclosure] First, embodiments of this disclosure will be described.

[0011] (1) The carbon nanotube composite disclosed herein comprises carbon nanotubes and core-shell nanoparticles attached to the carbon nanotubes, wherein the core-shell nanoparticles comprise a core composed of iron and a shell containing iron and sulfur covering the core, wherein the percentage of the number of sulfur atoms in the core-shell nanoparticles relative to the total number of iron and sulfur atoms is 6% or more and 45% or less.

[0012] According to this disclosure, a carbon nanotube composite that is a sulfur-containing material with good electrical conductivity can be provided.

[0013] If the percentage of sulfur atoms in core-shell nanoparticles relative to the combined percentage of iron and sulfur atoms is greater than 6%, the sulfur content of the carbon nanotube composite increases. Therefore, when the carbon nanotube composite is applied to the cathode of a lithium-sulfur battery, it helps to further improve the theoretical energy density of the lithium-sulfur battery. If this percentage is less than 6%, sulfur is insufficient relative to lithium during the charge and discharge process of the lithium-sulfur battery, thus failing to achieve sufficient energy density.

[0014] If the percentage of sulfur atoms relative to the total number of iron and sulfur atoms in core-shell nanoparticles is less than 45%, the conductivity of iron can be maintained. Therefore, when carbon nanotube composites are applied to the cathode of lithium-sulfur batteries, the electrochemical reaction between sulfur and lithium can be promoted during the charge-discharge process of lithium-sulfur batteries.

[0015] (2) Alternatively, in (1) above, the particle size of the core-shell nanoparticles is greater than 2 nm and less than 50 nm. If the particle size of the core-shell nanoparticles is greater than 50 nm, they cannot function as a catalyst for the synthesis of carbon nanotubes, the manufacturing efficiency of carbon nanotubes will be significantly reduced, and therefore good conductivity cannot be obtained, thus hindering the function of carbon nanotubes as conductive aids.

[0016] (3) Alternatively, in (1) or (2) above, the carbon content of the carbon nanotube composite is 50% by mass or more and 95% by mass or less. If the carbon content is 50% by mass or more, the conductivity of the carbon nanotube composite is improved. If the carbon content is 50% by mass or more, and the percentage of sulfur atoms in the core-shell nanoparticles relative to the total number of iron and sulfur atoms is 6% or more, then when the carbon nanotube composite is applied to the positive electrode of a lithium-sulfur battery, the theoretical energy density of the lithium-sulfur battery is further improved.

[0017] (4) The carbon nanotube composite assembly line of this disclosure is a carbon nanotube composite assembly line that includes multiple carbon nanotube composites as described in any one of (1) to (3) above.

[0018] According to this disclosure, it is possible to provide a carbon nanotube composite wire containing sulfur and having good electrical conductivity.

[0019] (5) Alternatively, in (4) above, the carbon content of the carbon nanotube composite wire is 50% by mass or more and 95% by mass or less. If the carbon content is 50% by mass or more, the conductivity of the carbon nanotube composite wire is improved. If the carbon content is 50% by mass or more, and the percentage of sulfur atoms in the core-shell nanoparticles relative to the total number of iron and sulfur atoms is 6% or more, then when the carbon nanotube composite wire is applied to the positive electrode of a lithium-sulfur battery, the theoretical energy density of the lithium-sulfur battery is further improved.

[0020] [Details of the embodiments disclosed herein] Hereinafter, specific examples of the carbon nanotube composites and carbon nanotube composite assembly lines of this disclosure will be described with reference to the accompanying drawings. In the accompanying drawings of this disclosure, the same reference numerals indicate the same or equivalent parts. In addition, the dimensional relationships such as length, width, thickness, and depth have been appropriately modified for the clarity and simplification of the drawings, and do not necessarily represent the actual dimensional relationships.

[0021] In this specification, expressions such as "A~B" refer to A and below B. If no unit is specified in A, but a unit is specified only in B, then the unit of A is the same as the unit of B.

[0022] In this disclosure, when more than one value is recorded as the lower limit and the upper limit of the numerical range, a combination of any value recorded in the lower limit and any value recorded in the upper limit is also disclosed.

[0023] [Implementation Method 1: Carbon Nanotube Composite] One embodiment of this disclosure (hereinafter also referred to as "Embodiment 1") involves a carbon nanotube composite comprising carbon nanotubes and core-shell nanoparticles attached to the carbon nanotubes. The core-shell nanoparticles comprise a core composed of iron and a shell containing iron and sulfur covering the core. The percentage of sulfur atoms in the core-shell nanoparticles relative to the total number of iron and sulfur atoms is 6% or more and 45% or less.

[0024] The carbon nanotube composite of Embodiment 1 has good electrical conductivity because it contains carbon nanotubes with excellent electrical conductivity.

[0025] The carbon nanotube composite of Embodiment 1 comprises core-shell nanoparticles attached to carbon nanotubes, wherein the percentage of sulfur atoms in the core-shell nanoparticles relative to the total number of iron and sulfur atoms is 6% or more and 45% or less. Because the core-shell nanoparticles contain sulfur, they can be used as the positive electrode in lithium-sulfur batteries.

[0026] <Structure of carbon nanotube composites> The carbon nanotube composite of Embodiment 1 comprises carbon nanotubes and core-shell nanoparticles attached to the carbon nanotubes. As long as the core-shell nanoparticles are attached to the carbon nanotubes, there are no particular restrictions on the location or morphology of the attachment. The core-shell nanoparticles can be attached to the ends of the carbon nanotubes or to areas other than the ends. At least a portion of the core-shell nanoparticles can also be embedded inside the carbon nanotubes. The number of core-shell nanoparticles attached to a carbon nanotube composite can be one or more. The presence of core-shell nanoparticles in the carbon nanotube composite is confirmed by observing the carbon nanotube composite at magnification of 100,000 to 1,500,000 times using a transmission electron microscope.

[0027] Carbon nanotubes Carbon nanotubes (hereinafter also referred to as "CNTs") can be CNTs with known structures. For example, they can be monolayer CNTs formed by a single layer of carbon (graphene) in a cylindrical shape, or bilayer or multilayer CNTs formed by stacking multiple carbon layers in a cylindrical shape, or cup-type CNTs formed by stacking graphene layers with the shape of a bottomless paper cup.

[0028] The shape of CNTs is not particularly limited; they can be either closed at the front end or open at the front end. Conical sections made of conical graphene can also be formed at one or both ends of the CNT.

[0029] The length of CNTs can be appropriately selected according to the application. The length of CNTs can be greater than 1 μm and less than 600 mm, greater than 10 μm and less than 600 mm, or greater than 100 μm and less than 600 mm. The length of CNTs is determined by observation using a scanning electron microscope.

[0030] The diameter of CNTs can be greater than 0.6nm and less than 20nm, greater than 0.7nm and less than 10nm, or greater than 0.8nm and less than 5nm.

[0031] In this disclosure, the diameter of a carbon nanotube refers to the average outer diameter of a CNT. The average outer diameter of a CNT is obtained by directly observing a cross-section of any two locations of the CNT using a transmission electron microscope. In this cross-section, the distance between the two furthest points on the outer periphery of the CNT, i.e., the outer diameter, is measured, and the average value of the resulting outer diameter is calculated. When the CNT includes a tapered portion at one or both ends, the diameter is measured at the location where the tapered portion is removed.

[0032] Core-shell nanoparticles Core-shell nanoparticles consist of an iron core and a shell containing both iron and sulfur. These nanoparticles are derived from catalysts and co-catalysts used in the manufacture of CNT complexes. Examples of catalysts include ferrocene (Fe(C5H5)2). Examples of co-catalysts include thiophene (CS2) and sulfur (S8).

[0033] The nucleus may contain iron along with unavoidable impurities, to the extent that it does not impair the effects of this disclosure. Examples of unavoidable impurities include, for instance, iron carbide.

[0034] The shell may contain unavoidable impurities along with iron and sulfur, to the extent that it does not impair the effects of this disclosure. Examples of unavoidable impurities include, for instance, iron carbide.

[0035] In core-shell nanoparticles, the shell may cover the entire surface of the core. Without impairing the effects of this disclosure, a portion of the core's surface may also remain uncovered by the shell.

[0036] Core-shell nanoparticles can also consist of an iron core and a shell containing iron and sulfur covering the core. Core-shell nanoparticles can contain carbon and oxygen in addition to the core and shell, without impairing the effects of this disclosure.

[0037] The fact that core-shell nanoparticles consist of an iron core and a shell containing iron and sulfur was confirmed by energy dispersive X-ray spectroscopy (EDX) or electron energy loss spectroscopy (EELS) attached to a transmission electron microscope (TEM).

[0038] The percentage of sulfur atoms in core-shell nanoparticles relative to the total number of iron and sulfur atoms (hereinafter also referred to as "sulfur content of core-shell nanoparticles") is 6% or more and 45% or less, or it can be 10% or more and 40% or less, or it can be 20% or more and 35% or less.

[0039] In this disclosure, the method for determining the percentage of sulfur atoms relative to the total number of iron and sulfur atoms in core-shell nanoparticles is as follows. Using an energy-dispersive X-ray spectrophotometer attached to a scanning electron microscope (SEM), characteristic X-rays originating from iron (Fe-Kα rays) and characteristic X-rays originating from sulfur (S-Kα rays) are measured in the carbon nanotube composite. The atomic ratio of sulfur to iron is calculated from these signal intensities and correction factors.

[0040] When a carbon nanotube composite contains multiple core-shell nanoparticles, the above-described measurements are performed on each of the core-shell nanoparticles individually. In this disclosure, a sulfur content of 6% or more and 45% or less in the core-shell nanoparticles means that the sulfur content of each of the multiple core-shell nanoparticles contained in a carbon nanotube composite is within the range of 6% or more and 45% or less. The same meaning applies to other numerical ranges.

[0041] The particle size of core-shell nanoparticles can be greater than 2 nm and less than 50 nm, greater than 4 nm and less than 25 nm, or greater than 6 nm and less than 10 nm.

[0042] In this disclosure, the method for determining the particle size of core-shell nanoparticles is as follows. First, a carbon nanotube composite is added to ethanol and dispersed by ultrasonic irradiation. The dispersion is then dropped onto a dedicated grid and dried. Next, it is observed using a transmission electron microscope (TEM) at a magnification of 100,000 to 1,500,000 times. Then, in the TEM image, the outer diameter, which is the distance between the two furthest points on the outer periphery of each core-shell nanoparticle, is measured. This outer diameter corresponds to the particle size of the core-shell nanoparticle.

[0043] When a carbon nanotube composite contains multiple core-shell nanoparticles, the above measurements are performed on all core-shell nanoparticles individually. In this disclosure, a particle size of 2 nm or more and 50 nm or less for core-shell nanoparticles means that the particle size of each of the multiple core-shell nanoparticles contained in a carbon nanotube composite is within the range of 2 nm or more and 50 nm or less. The same meaning applies to other numerical ranges.

[0044] The particle size of the nucleus can be greater than 1 nm and less than 48 nm, greater than 2 nm and less than 23 nm, or greater than 3 nm and less than 8 nm.

[0045] The thickness of the shell can be greater than 0.5nm and less than 12nm, greater than 1nm and less than 6nm, or greater than 1.5nm and less than 3nm.

[0046] In this disclosure, the method for determining the core particle size and the average thickness of the shell is as follows. First, the core-shell nanoparticles are observed using a transmission electron microscope (TEM) at a magnification of 100,000 to 1,500,000 times. Then, in the same field of view, a two-dimensional mapping image of the signals originating from the Fe-Fe bonds (core region) and Fe-S bonds (shell region) is measured using an electron energy loss spectrophotometer (EELS) attached to the TEM. The outer diameter, i.e., the distance between the two furthest points on the outer periphery of the region corresponding to the core, is measured. This outer diameter corresponds to the core particle size. The shell thickness is calculated based on the difference between the core-shell nanoparticle size and the core particle size.

[0047] <Coarse particles> Carbon nanotube composites can also be free of coarse particles larger than 50 nm. These coarse particles are formed when ferrocene (Fe(C5H5)2), acting as a catalyst, decomposes during the fabrication of carbon nanotube composites, resulting in the formation and coarsening of iron particles. These coarse particles do not contribute to the synthesis of CNTs and affect their electrical conductivity. If the carbon nanotube composite does not contain these coarse particles, the CNTs can maintain their inherent electrical conductivity.

[0048] The absence of coarse particles in the carbon nanotube composite was confirmed by observing the composite using TEM. The composition of coarse particles was determined using energy-dispersive X-ray diffraction (TEM-EDX) equipment attached to the TEM.

[0049] <Carbon content of carbon nanotube composites> The carbon content of the carbon nanotube composite can be above 50% by mass and below 95% by mass, or above 55% by mass and below 90% by mass, or above 60% by mass and below 85% by mass.

[0050] The carbon content of the carbon nanotube composite was determined by thermogravimetric analysis (TGA). The specific method is as follows: A sample of approximately 1–5 mg of carbon nanotube composite was weighed and heated from 30 °C to 1000 °C at a rate of 3 °C / min while circulating dry air (N₂:O₂ = 8:2) at a flow rate of 200 mL / min. The weight change of the sample was measured. The carbon components in the sample burned within the range of 300–900 °C, releasing gases such as carbon dioxide, thus reducing the weight. Further heating to 1000 °C resulted in complete combustion of the carbon components. The weight of the remaining sample after complete combustion was equivalent to the content of catalyst particles before combustion. Therefore, the carbon content was calculated by determining the content of the catalyst particles.

[0051] <Manufacturing Methods of Carbon Nanotube Composites> To deepen the understanding of the manufacturing method of the carbon nanotube composite in Embodiment 1, a conventional manufacturing method for carbon nanotube composites will first be described. Conventional carbon nanotube composites, for example, use... Figure 1 The carbon nanotube composite manufacturing apparatus 10 shown is manufactured by an airflow method.

[0052] The carbon nanotube composite manufacturing apparatus 10 may include: a quartz tube 12; a sprayer 13 disposed on one of the first ends 12c of the quartz tube 12, supplying carbon source gas (methane, ethylene, acetone, etc.), a catalyst raw material containing a catalyst (ferrocene) and a co-catalyst (thiophene, sulfur (S8) etc.) and hydrogen as a carrier gas into the quartz tube 12; and an electric furnace 11 for heating the quartz tube 12.

[0053] The electric furnace 11 heats the quartz tube 12 to bring its interior to the CNT synthesis temperature (approximately 1200-1500°C). The carbon source gas supplied to the interior of the quartz tube 12, as well as the components contained in the catalyst raw material liquid, undergo thermal decomposition. The thermal decomposition temperature of ferrocene is approximately 400-500°C, that of thiophene is approximately 750-850°C, and that of the carbon source is approximately 800-1050°C.

[0054] The internal region on the first end 12c side of the quartz tube 12 (hereinafter also referred to as the "radiative heat-receiving region") has a temperature of approximately 400~900°C due to the radiative heat from the electric furnace 11. In the radiative heat-receiving region 12e, iron particles formed by the thermal decomposition of ferrocene and sulfur (S2) formed by the decomposition of thiophene or sulfur (S8) are used to form core-shell nanoparticles containing a core composed of iron as iron particles and a shell containing iron and sulfur covering the core.

[0055] The internal region of the quartz tube 12, located downstream of the radiative heating region 12e and opposite the electric furnace (hereinafter also referred to as the "electric furnace heating region"), is at approximately 1200~1500°C, which is the CNT synthesis temperature. Core-shell nanoparticles that move to the electric furnace heating region 12f with the flow of carrier gas are supplied with carbon from the carbon source decomposition, thereby growing carbon nanotubes from the core-shell nanoparticles to form a carbon nanotube composite.

[0056] In conventional carbon nanotube manufacturing methods, the quartz tube 12 is heated to approximately 1200-1500°C, the synthesis temperature for carbon nanotubes. Therefore, the length of the radiatively heated region 12e, which has the temperature necessary to form core-shell nanoparticles, along the long side of the quartz tube 12 is very short, even shorter than the length of the electric furnace heating region 12f along the same long side. In the gas flow method, a gas containing carbon source gas and catalyst feedstock liquid (hereinafter also referred to as "feedstock gas") passes continuously from the first end 12c side to the second end 12d side. Therefore, the time for the feedstock gas to pass through the radiatively heated region 12e is very short (far less than 1 second), resulting in insufficient time for core-shell nanoparticle formation. Consequently, along with the core-shell nanoparticles, the catalyst and co-catalyst remain intact, or coarse particles formed by the coarsening of iron particles are formed. Furthermore, even when core-shell nanoparticles are formed, the iron particles are excessively coated with sulfur. Therefore, in conventional carbon nanotube manufacturing methods, the percentage of sulfur atoms relative to the total number of iron and sulfur atoms in the core-shell nanoparticles is 46% or more. Consequently, conventional carbon nanotube manufacturing methods do not produce core-shell nanoparticles containing an iron core and a shell with iron and sulfur coating, and the percentage of sulfur atoms relative to the total number of iron and sulfur atoms in the core-shell nanoparticles is 6% or more and 45% or less.

[0057] In order to obtain the carbon nanotube composite of Embodiment 1, the inventors of this invention have focused particularly on the formation process of core-shell nanoparticles and created a new manufacturing method. The manufacturing method of the carbon nanotube composite of Embodiment 1 will be described below. The carbon nanotube composite of Embodiment 1 is, for example, produced using... Figure 2 The carbon nanotube composite manufacturing apparatus 10 shown is prepared by an airflow method.

[0058] The carbon nanotube composite manufacturing apparatus 10 may include: a quartz tube 12; a sprayer 13 disposed on one of the first ends 12c of the quartz tube 12, supplying carbon source gas (methane, ethylene, acetone, etc.), a catalyst raw material containing a catalyst (ferrocene) and a co-catalyst (thiophene, sulfur (S8), etc.) and hydrogen as a carrier gas into the quartz tube 12; and a first electric furnace 11a and a second electric furnace 11b for heating the quartz tube 12.

[0059] The internal region 12a of the quartz tube 12, located at the first end 12c opposite to the first electric furnace 11a, is heated by the first electric furnace 11a to approximately 800-1000°C, a temperature at which core-shell nanoparticles can be formed. The internal region 12b of the quartz tube 12, located at the second end 12d opposite to the second electric furnace 11b, is heated by the second electric furnace 11b to approximately 1200-1500°C, a temperature at which carbon nanotubes can be synthesized.

[0060] In the carbon nanotube composite manufacturing apparatus 10, the length of the first region 12a along the long side of the quartz tube 12 is sufficiently long compared to the length along the long side of the radiatively heated region 12e corresponding to the first region 12a in conventional carbon nanotube composite manufacturing apparatuses. Therefore, in the carbon nanotube composite manufacturing apparatus 10, the time for the gas containing the carbon source gas and the catalyst feedstock liquid to pass through the first region 12a is extended (e.g., 1 second or more), sufficiently ensuring the formation time of core-shell nanoparticles. Thus, in the carbon nanotube composite manufacturing apparatus 10, it is possible to form core-shell nanoparticles comprising an iron core and a shell containing both iron and sulfur, wherein the percentage of sulfur atoms in the core-shell nanoparticles relative to the total number of iron and sulfur atoms is 6% or more and 45% or less. Furthermore, it is also possible to suppress the presence of residual catalyst or co-catalyst, or the formation of coarse iron particles.

[0061] The ratio of the lengths of the first region 12a to the second region 12b along the long side of the quartz tube 12 can be, for example, 1:1 to 1:10.

[0062] The length of the first region 12a along the long side of the quartz tube 12 can be, for example, 100 to 1000 mm. The length of the second region 12b along the long side of the quartz tube 12 can be, for example, 300 to 1000 mm.

[0063] The overall flow velocity of the carrier gas and the gas-containing feedstock in the first region 12a can, for example, be 0.4 to 10 cm / s. The overall flow velocity of the carrier gas and the gas-containing feedstock in the second region 12b can also, for example, be 0.4 to 10 cm / s.

[0064] The second region 12b of the quartz tube 12 is located at approximately 1200-1500°C, which is the CNT synthesis temperature. The core-shell nanoparticles that move to the second region 12b with the flow of gas-containing raw materials are supplied with carbon formed by the decomposition of a carbon source, thereby growing carbon nanotubes from the core-shell nanoparticles to form the carbon nanotube composite of Embodiment 1.

[0065] [Implementation Method 2: Carbon Nanotube Composite Assembly Line] The carbon nanotube composite assembly line involved in one embodiment of this disclosure (hereinafter also referred to as "Embodiment 2") is a carbon nanotube composite assembly line that includes multiple carbon nanotube composites of Embodiment 1.

[0066] Since the carbon nanotube composite wires in Embodiment 2 have excellent conductivity, they also have good conductivity.

[0067] The carbon nanotube composite assembly of Embodiment 2 comprises core-shell nanoparticles attached to carbon nanotubes, wherein the percentage of sulfur atoms in the core-shell nanoparticles relative to the total number of iron and sulfur atoms is 6% or more and 45% or less. Because the core-shell nanoparticles contain sulfur, they can be used as the positive electrode in lithium-sulfur batteries.

[0068] The carbon nanotube composite assembly line of Embodiment 2 can also be composed of multiple carbon nanotube composites of Embodiment 1. Furthermore, the carbon nanotube composite assembly line of Embodiment 2 may also include multiple carbon nanotube composites of Embodiment 1 and carbon nanotubes without attached core-shell nanoparticles. Additionally, the carbon nanotube composite assembly line of Embodiment 2 may include carbon nanotube composites and components other than carbon nanotubes, to the extent that it does not impair the effects of this disclosure. Other components include, for example, fullerenes, graphene, amorphous carbon, and polymers used as binders for electrodes.

[0069] The shape of the carbon nanotube composite assembly line in Embodiment 2 is not particularly limited and can be appropriately set according to the application. For example, the shape of the carbon nanotube composite assembly line can be a line formed by multiple carbon nanotube composites oriented and assembled along their long side.

[0070] The length of the carbon nanotube composite aggregate line in Embodiment 1 is not particularly limited and can be appropriately set according to the application. The length of the CNT composite aggregate line can be, for example, 100 μm or more and 100 m or less, 1000 μm or more and 100 m or less, or 10 cm or more and 100 m or less. The length of the CNT composite aggregate line is determined by scanning electron microscopy, optical microscopy or visual observation.

[0071] The diameter of the carbon nanotube composite aggregate wire in Embodiment 1 is not particularly limited and can be appropriately set according to the application. For example, the diameter of the CNT composite aggregate wire can be 0.1 μm or more and 100 μm or less, or it can be 1 μm or more and 100 μm or less. The diameter of the CNT composite aggregate wire is smaller than the length of the CNT aggregate wire. That is, the length direction of the CNT composite aggregate wire corresponds to the long side direction.

[0072] In this disclosure, the diameter of a carbon nanotube composite assembly line refers to the average outer diameter of such an assembly line. The method for determining the average outer diameter of a carbon nanotube composite assembly line is as follows: A cross-section at any two locations on the carbon nanotube composite assembly line is observed using a transmission electron microscope or a scanning electron microscope. Within this cross-section, the outer diameter of the distance between the two furthest points on the outer periphery of the carbon nanotube composite assembly line is measured. The average outer diameter at the two locations is calculated. This average value corresponds to the diameter of the carbon nanotube composite assembly line.

[0073] In carbon nanotube (CNT) composite aggregates, core-shell nanoparticles can also exist dispersedly along the long side of the CNT composite aggregate. Here, "dispersion of core-shell nanoparticles along the long side of the CNT composite aggregate means that the core-shell nanoparticles exist without bias along the long side of the CNT composite aggregate. Therefore, the core-shell nanoparticles do not affect the conductivity of CNTs, and the CNT composite aggregate can achieve long-size CNTs while maintaining their inherent conductivity.

[0074] The dispersion of core-shell nanoparticles contained in the CNT complex aggregate line along the long side of the CNT complex aggregate line can be confirmed by EDX and electron energy loss spectrometry (EELS), which can be performed simultaneously with electron microscopes such as SEM and TEM.

[0075] The carbon content of the carbon nanotube composite wire can be above 50% by mass and below 95% by mass, or above 55% by mass and below 90% by mass, or above 60% by mass and below 85% by mass.

[0076] The carbon content of the carbon nanotube composite aggregate wires was determined by thermogravimetric analysis. The specific method of thermogravimetric analysis is as described in Embodiment 1.

[0077] <Manufacturing Method of Carbon Nanotube Composite Assemblies> The carbon nanotube composite assembly line of Embodiment 2 can be manufactured by aligning and assembling multiple carbon nanotube composites of Embodiment 1 along the long side direction.

[0078] Example The present embodiment will be described in more detail through examples. However, the present embodiment is not limited to these examples.

[0079] <Device 1> As device 1, using a Figure 2 The apparatus shown is used to manufacture carbon nanotube composites. The quartz tube 12 has an inner diameter of 46 mm and a length of 1200 mm. The first electric furnace 11a has a length of 500 mm, and the second electric furnace 11b has a length of 500 mm.

[0080] <Device 2> As device 2, using a Figure 1 The apparatus shown is used to manufacture carbon nanotube composites. The quartz tube 12 has an inner diameter of 46 mm and a length of 1200 mm. The electric furnace 11 has a length of 1000 mm.

[0081] <Preparation of Carbon Nanotube Composites> Using apparatus 1, carbon nanotube composites of samples 1 to 9 were prepared. Using apparatus 2, carbon nanotube composites of samples 1-1 to 1-3 were prepared. The specific manufacturing methods are described below.

[0082] Ferrocene and thiophene were dissolved in toluene to prepare a catalyst feedstock containing liquid. The ferrocene content in the catalyst feedstock containing liquid was 4% by mass. In each sample, the thiophene content in the catalyst feedstock liquid was adjusted so that the atomic ratio of iron to sulfur in the catalyst feedstock liquid was the ratio shown in the "Fe:S" column of "Catalyst Feedstock Containing Liquid" in Table 1.

[0083] In both apparatus 1 and apparatus 2, hydrogen gas with a concentration of 100% by volume is supplied from the sprayer 13 into the internal space of the quartz tube at a flow rate of 7 L / min (flow velocity 7 cm / s) while the temperature inside the electric furnace is increased. In each sample using apparatus 1, the temperatures of the first region 12a inside the quartz tube 12 opposite to the first electric furnace 11a and the second region 12b inside the quartz tube 12 opposite to the second electric furnace 11b are shown in the "Temperature" column of "First Region" and the "Temperature" column of "Second Region" in Table 1, respectively. In each sample using apparatus 2, the overall internal temperature of the quartz tube 12 is 1400°C.

[0084] Next, while hydrogen gas was introduced, ethylene gas was supplied from the sprayer 13 into the internal space of the quartz tube at a flow rate of 50 mL / min (flow velocity 0.05 cm / s), and catalyst feedstock liquid was supplied at a flow rate of 0.1 mL / min (flow velocity 0.02 cm / s) for 5 minutes. The overall flow rate of the gas including hydrogen, ethylene gas, and catalyst feedstock liquid was 7.07 cm / s.

[0085] Subsequently, the carbon nanotube composite formed inside the quartz tube was recovered.

[0086]

[0087] [Evaluation of carbon nanotube composites] <Observations under a transmission electron microscope> The carbon nanotube composites of each sample were observed using a transmission electron microscope at 200,000x magnification. Carbon nanotubes and particles attached to them were confirmed in all samples. The transmission electron microscope image of the carbon nanotube composite obtained in sample 5 is shown below. Figure 3 .

[0088] <Determination of Core-Shell Nanoparticles> In the carbon nanotube composites of each sample, the percentage of sulfur atoms in the core-shell nanoparticles relative to the total number of iron and sulfur atoms was determined. The specific determination method is as described in Example 1. The results are shown in the "S / (Fe+S)" column of "Core-shell Nanoparticles" in Table 2. For example, the "40~45%" recorded for Sample 1 indicates that the sulfur content of each of the multiple core-shell nanoparticles contained in a carbon nanotube composite is in the range of 40~45% (i.e., the minimum value is 40% and the maximum value is 45%).

[0089] The particle size of the core-shell nanoparticles in the carbon nanotube composites of each sample was measured. The specific measurement method is as described in Example 1. The results are shown in the "Particle Size" column of "Core-shell Nanoparticles" in Table 2. For example, the description of "3~40 nm" for sample 1 indicates that the particle size of each of the multiple core-shell nanoparticles contained in a carbon nanotube composite is in the range of 3~40 nm (i.e., the minimum value is 3 nm and the maximum value is 40 nm).

[0090] <Determination of Carbon Nanotubes> In the carbon nanotube composites of each sample, the length and diameter of the carbon nanotubes were measured. The specific measurement method is as described in Embodiment 1. The results are shown in the "Length" and "Diameter" columns of "CNT" in Table 2. For example, the description of the length of sample 1 as "1~100 μm" indicates that multiple carbon nanotube composites were prepared in each sample, and the length of the carbon nanotubes contained in each composite is in the range of 1~100 μm (i.e., the minimum value is 1 μm and the maximum value is 100 μm). The same applies to the diameter.

[0091] <Determination of carbon content in carbon nanotube composites> The carbon content of the carbon nanotube composites in each sample was determined. The specific determination method is as described in Example 1. The results are shown in the "Carbon Content" column of "CNT Composites" in Table 2.

[0092] <Presence or absence of coarse particles> In each sample, multiple carbon nanotube composites were observed using a transmission electron microscope at 200,000x magnification. No coarse particles larger than 50 nm were identified in samples 1-9. In samples 1-1-1-3, coarse particles larger than 50 nm were found attached to a portion of the carbon nanotube composites.

[0093] <Observation of the aggregation lines of carbon nanotube complexes> In each sample, carbon nanotube composite aggregates were also prepared into carbon nanotube composite aggregate lines. The carbon content of the carbon nanotube composite aggregate lines of samples 1 to 9 was the same as the carbon content of the carbon nanotube composites. In addition, in the carbon nanotube composite aggregate lines of samples 1 to 9, core-shell nanoparticles were found to be dispersed along the long side of the CNT composite aggregate line.

[0094]

[0095] In the carbon nanotube composites and carbon nanotube composite aggregates of samples 1 to 9, the percentage of sulfur atoms in the core-shell nanoparticles relative to the total number of iron and sulfur atoms is 25% or more and 45% or less, which is equivalent to the example.

[0096] In the carbon nanotube composites and carbon nanotube composite aggregates of samples 1-1 to 1-3, the percentage of sulfur atoms in the core-shell nanoparticles relative to the total number of iron and sulfur atoms is more than 46%, which is equivalent to the comparative example.

[0097] The embodiments and examples of this disclosure have been described above, but it is also intended from the outset that the above-described embodiments and examples may be appropriately combined or modified.

[0098] The embodiments and examples disclosed herein should be considered exemplary in all respects, and not restrictive. The scope of the invention is defined not by the foregoing embodiments and examples, but by the claims, and is intended to include all modifications equivalent to and within the scope of the claims.

[0099] Explanation of reference numerals in the attached figures 1: Carbon nanotubes; 2: Core-shell nanoparticles; 3: Carbon nanotube composite assembly line; 10: Carbon nanotube composite manufacturing device; 11: Electric furnace; 11a: First electric furnace; 11b: Second electric furnace; 12: Quartz tube; 12a: First region; 12b: Second region; 12c: First end; 12d: Second end; 12e: Radiant heat-receiving region; 12f: Electric furnace heating region; 13: Sprayer.

Claims

1. A carbon nanotube composite, wherein, The carbon nanotube composite comprises carbon nanotubes and core-shell nanoparticles attached to the carbon nanotubes. The core-shell nanoparticles comprise an iron core and a shell containing iron and sulfur enclosing the core. The percentage of sulfur atoms in the core-shell nanoparticles relative to the total number of iron and sulfur atoms is 6% or more and 45% or less.

2. The carbon nanotube composite according to claim 1, wherein, The core-shell nanoparticles have a particle size of 2 nm or more and 50 nm or less.

3. The carbon nanotube composite according to claim 1 or 2, wherein, The carbon nanotube composite has a carbon content of more than 50% by mass and less than 95% by mass.

4. A carbon nanotube composite assembly line, wherein, The carbon nanotube composite assembly line comprises a plurality of carbon nanotube composites as described in any one of claims 1 to 3.

5. The carbon nanotube composite assembly line according to claim 4, wherein, The carbon content of the carbon nanotube composite assembly is above 50% by mass and below 95% by mass.

Citation Information

Patent Citations

  • Nail clipper

    JP2024054384A